Survey Impact of COVID on Work-Family Conflict (WFC) and Flexible Work Arrangement (FWA) - Hani Gita Ayuningtias; Annisa Nurbaiti; Ratih Hendayani; Setiadi Setiadi (Jurnal Manajemen Indonesia, 2023)
Covid is mandating that all businesses around the globe be able to accommodate flexible work schedules. In addition, many companies are instituting work-from-home policies due to social interaction restrictions. This condition makes it difficult for businesses to establish explicit FWA regulations. The implementation of a WFA presents numerous obstacles, particularly concerning WFC. Certain conditions will have a negative impact on employees who are tasked with completing work in addition to domestic responsibilities. If no distinct rules govern this, it will be difficult for employees to manage their time, negatively impacting employee performance. Members continue to believe that the FWA settings are not optimal one year after the pandemic has begun. Many employees still confront WFC when completing work and homework simultaneously. This condition stipulates that implementing FWA must be enhanced to reduce the risk of WFC. The data acquisition method is a survey of 100 employees in the manufacturing industry that produces steel. According to the study's findings, the Work-Family Conflict (WFC) was in the lowest category, with employees believing that the tasks assigned are balanced between work and family to avoid creating work-family conflicts. While the FWA implementation was rated acceptable, it makes it easier for employees to manage their time more flexibly to complete their work. The obtained results can assist the organization in enhancing its procedures for implementing the FWA. Keywords—Work-Family Conflict; Flexible Work Arrangement